2022
DOI: 10.5114/aoms/153500
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic potential of novel biomarkers of hypertension in men

Abstract: IntroductionThe present study aimed to evaluate the diagnostic usefulness of selected novel parameters as biomarkers of hypertension: miR-145-5p, miR-1-3p, miR-423-5p, PCSK9, MyBPC3, NOX1, CYBb, and NCF2, DNase 1, anti-MPO and anti-PR3 antibodies.Material and methodsWe present the data of men with normal blood pressure, diagnosed hypertension, confirmed hypertension, hypertension and coexisting coronary artery disease.ResultsElevated levels of miR-145-5p, miR-1-3p, and miR-423-5p and high levels of PCSK9, MyBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On the other hand, Jayedi et al performed a meta-analysis [11] and showed that there was a relationship between inflammatory markers (hs-CRP and IL-6) and the risk of developing hypertension in a prospective or nested case-control study. Some studies evaluated PCSK9 as an early biomarker of screening-detected hypertension [21]. Our study was cross-sectional; therefore, it was not possible to assess a causal association between inflammation and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Jayedi et al performed a meta-analysis [11] and showed that there was a relationship between inflammatory markers (hs-CRP and IL-6) and the risk of developing hypertension in a prospective or nested case-control study. Some studies evaluated PCSK9 as an early biomarker of screening-detected hypertension [21]. Our study was cross-sectional; therefore, it was not possible to assess a causal association between inflammation and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting DNA–RNA hybrids are transferred to wells in microplates coated with a monoclonal antibody specific for DNA–RNA hybrids. After washing, the solid phase is incubated with the streptavidin–horseradish peroxidase (HRP) conjugate, and after another washing step, the resulting complexes are visualised by adding a chromogenic substrate (Krepelkova et al ., 2019; Dawidowicz et al ., 2021; Charkiewicz et al ., 2022).…”
Section: Methods To Evaluate Mirna Expressionmentioning
confidence: 99%
“…Interestingly, circulating miR-423–5p levels were found to be reduced shortly after a severe myocardial infarction, followed by an increase after five months in the same group of patients, highlighting the dynamic nature of miRNA levels. Discrepancies in miRNA levels among various research centers may stem from differences in study methods, patient selection, age, sex, or ethnicity ( 121 ). Liang et al.…”
Section: Mirnas As Diagnostic Biomarkers In Hypertensionmentioning
confidence: 99%